Post-processing method for improving high-pressure impact damage threshold value of sapphire optical element

The deposits are removed by etching of high-temperature inorganic acid solution and phosphoric acid, combined with NaOH solution and multi-band ultrasonication, and finally, alternating ultrasound and rinsing of surfactant and deionized water, the problem of high damage threshold of sapphire optical components under high pressure shock was solved, and the impact resistance life was significantly improved.

CN119736719APending Publication Date: 2025-04-01LASER FUSION RES CENT CHINA ACAD OF ENG PHYSICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411938352.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The damage threshold of sapphire optical components is very random under high pressure shock, which affects the stability and life of use under extreme service conditions. The existing polishing processes and reactive ion etching methods have problems of instability and high cost.

Method used

The surface morphology of sapphire optical elements was detected by confocal microscope, and subsurface defects were removed by etching with high temperature inorganic acid solution. Subsequently, sediments were removed using phosphoric acid, combined with NaOH solution and multi-band ultrasonication, and finally, the depth removal was performed using alternating ultrasound and rinsing of surfactant and deionized water.

Benefits of technology

Effectively passivate subsurface defects, prevent stress concentration under high-pressure impact, and significantly improve the impact damage threshold and impact resistance life of sapphire optical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736719A_ABST
    Figure CN119736719A_ABST
Patent Text Reader

Abstract

The invention discloses a post-processing method for improving a high-pressure impact damage threshold of a sapphire optical element, which comprises the following steps: exposing and passivating subsurface defects through high-temperature chemical corrosion reaction, and removing insoluble reaction sediments through phosphoric acid reaction at high temperature; afterwards, removing redundant acidic materials through a NaOH solution assisted by multi-frequency ultrasonic wave alternate multiplexing; and finally, rinsing through high-purity water and a surfactant assisted by multi-frequency ultrasonic wave alternate multiplexing. The sapphire optical element can be globally treated, a deposition layer is removed and scratches and pits in a subsurface layer are exposed through corrosion treatment of a mixed solution of sulfuric acid and phosphoric acid in a specific proportion at a high temperature and phosphoric acid dissolution, and sharp shapes in the scratches are effectively passivated, so that the sapphire high-pressure impact damage threshold value is effectively increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of optical element processing and machining, and in particular relates to a post-processing method for improving a high-voltage impact damage threshold of a sapphire optical element. Background Art

[0002] Sapphire has excellent optical and mechanical properties and is often used as a window material in various extreme conditions, such as optoelectronic windows commonly used in high-speed flights and observation windows in high-pressure impact experiments. With the increasing demand for these extreme service conditions, the randomness of the damage threshold of sapphire optical components under high-pressure impact has greatly affected the stability of various special systems and increased the cost of system operation. Therefore, the current impact damage threshold of sapphire optical components is the main technical shortcoming that limits the service life under these extreme service conditions. According to recent research results, the mechanical polishing of optical components will inevitably cause damage defects and cracks to form in the sub-surface layer of brittle materials; solid particles in the polishing liquid are embedded in the sub-surface layer to form a redeposition layer of hundreds of nanometers, such as SiO 2 and diamond, etc. These damage defects and redeposition layer defects may act as damage precursors when subjected to high-pressure impact, forming microcracks, leading to accelerated aging of optical components and causing more serious damage. Therefore, this randomly distributed sub-surface defect will cause an uncertain distribution of the sapphire's impact pressure resistance life distribution. At present, the main method to enhance the surface quality of sapphire is to improve the polishing process, such as changing the polishing material or reactive ion etching. However, polishing materials are all hard materials, and surface treatment of brittle materials such as sapphire will always bring about damage instability. Reactive ion etching is costly and lacks flexibility in processing small-sized components. Therefore, a single reactive ion etching can no longer meet the actual engineering needs. It is urgent to explore a surface post-treatment method that can effectively improve the ability of sapphire optical components to resist high-pressure impact to solve the above technical problems. Summary of the invention

[0003] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0004] In order to achieve these purposes and other advantages according to the present invention, a post-processing method for improving the high-voltage impact damage threshold of a sapphire optical element is provided, comprising the following steps:

[0005] S1. Use confocal microscopy to detect the surface morphology of sapphire optical components;

[0006] S2, heating and etching the subsurface defect layer on the surface of the sapphire optical element with an inorganic acid solution, passivating the scratches, cracks and pits on the subsurface of the sapphire optical element by high-temperature wet etching; then replacing the etching solution with phosphoric acid to remove the reactants deposited on the surface of the sapphire optical element;

[0007] S3, the sapphire optical element with surface deposits removed is rinsed with high-purity water, then immersed in NaOH solution, supplemented with multi-band ultrasonic treatment, and then rinsed with high-purity water;

[0008] S4. Soak the sapphire component in a surfactant and treat it with multiple frequency bands of ultrasonic waves. Finally, use high-purity water for ultrasonic cleaning and direct rinsing, and dry it naturally.

[0009] Preferably, in S2, the inorganic acid solution is a mixed acid of sulfuric acid and phosphoric acid, the mixing ratio is sulfuric acid: phosphoric acid = 4:1 to 1:4, the etching time is 5 to 300 min, the temperature is 200 to 240°C, the sulfuric acid concentration is 95 to 99 vol%, and the phosphoric acid concentration is 80 to 90 vol%.

[0010] Preferably, in S2, the temperature of phosphoric acid when removing surface deposits is 160-220°C, and after the optical element is placed in the solution, the heating is stopped and the solution is naturally cooled to room temperature.

[0011] Preferably, in S3, the surface is first rinsed with high-purity water for 10 to 60 seconds, the concentration of the NaOH solution is 5% to 15%, the soaking temperature is 30 to 50°C, the soaking time is 10 to 60 minutes, the ultrasonic frequency is 20kHz to 135kHz and at least two frequencies are selected during ultrasonic treatment, and finally rinsed with high-purity water for 1 to 5 minutes.

[0012] Preferably, in S4, when a surfactant is used for soaking, the soaking liquid is prepared according to the ratio of surfactant to deionized water = 1:10, and the soaking is carried out for 30 to 60 minutes. Ultrapure water is then used for ultrasonic cleaning, and the ultrasonic frequency is 20kHz to 135kHz. At least two frequencies are selected during ultrasonic treatment, and the cleaning is carried out for 30 minutes. Finally, ultrapure water is sprayed and rinsed for 5 to 10 minutes, and the mixture is dried naturally.

[0013] Preferably, in S4, the surfactant comprises 10% wt to 25% wt of tetrasodium ethylenediaminetetraacetate, 5% wt to 15% wt of ammonium xylenesulfonate, 5% wt to 15% wt of benzenesulfonic acid, 0.05% wt

[0014] ~0.5%wt of sodium hydroxide and 44.5~69.95%wt of water.

[0015] Preferably, the surfactant in S4 is pretreated by the following method: after uniformly mixing 25%wt of tetrasodium ethylenediaminetetraacetate, 15%wt of ammonium xylenesulfonate, 15%wt of benzenesulfonic acid, 0.5%wt of sodium hydroxide, 4%wt of sodium carbonate, 6%wt of anhydrous sodium metasilicate and 30%wt of water by weight, stirring until completely dissolved for later use; then adding 2%wt of diethylene glycol monobutyl ether to 1.5%wt of nonylphenol polyoxyethylene ether, mixing well and then quickly adding to the previously prepared solution while stirring, and adding 1%wt of sodium dodecylbenzene sulfonate during the stirring process to obtain a pretreated surfactant.

[0016] The present invention includes at least the following beneficial effects: using a high-temperature acid etching method to expose sub-surface crushing defects and cracks caused by processing on the component surface, and removing the redeposition layer caused by abrasives, and passivating these defects, using a specific ratio of sulfuric acid and phosphoric acid, the etching rate can be effectively controlled, and the formation of insoluble matter during the reaction process can be avoided to affect the subsequent etching reaction; by soaking in high-temperature phosphoric acid and natural cooling, the insoluble matter formed in the previous high-temperature acid washing is removed, and the formation of thermal stress is avoided; the rinsing of deionized water and the multi-band ultrasonic cleaning of NaOH solution can effectively remove the high-viscosity phosphoric acid; the subsequent alternating ultrasonic and rinsing of surfactants and deionized water can further remove near-surface contaminants; through the above-mentioned post-processing technology, sub-surface defects and cracks can be effectively passivated to prevent stress concentration under impact pressure, thereby improving the impact damage threshold and impact resistance life of sapphire optical elements.

[0017] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a surface morphology image of the sapphire optical element A in Example 1 before post-processing;

[0019] Figure 2 This is a surface morphology image of the sapphire optical element A in Example 1 after post-processing;

[0020] Figure 3 This is an enlarged view of the surface morphology of the sapphire optical element A in Example 1 after post-processing;

[0021] Figure 4 for Figure 3 Depth information distribution diagram on the path shown by the red line in the middle;

[0022] Figure 5 This is an enlarged view of the surface morphology of the sapphire optical element B in Example 2 after post-processing;

[0023] Figure 6 for Figure 5 Depth information distribution diagram on the path shown by the red line in the middle;

[0024] Figure 7 This is a surface topography image of the sapphire optical element C in Example 3 before post-processing;

[0025] Figure 8 This is a surface morphology image of the sapphire optical element C in Example 3 after post-processing;

[0026] Fig. 9 This is an enlarged view of the surface morphology of the sapphire optical element C in Example 3 after post-processing;

[0027] Fig.10 Fig. 9 Depth information distribution diagram on the path shown by the red line in the middle;

[0028] Fig.11 The bending strength distribution of untreated sapphire;

[0029] Fig.12 The bending strength distribution of sapphire after post-processing;

[0030] Fig.13 This is the optical element of Comparative Example 6 that has not been subjected to multi-band ultrasound treatment. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0032] Example 1

[0033] A post-processing method for improving the high-voltage impact damage threshold of a sapphire optical element, comprising:

[0034] S1. Perform a pre-polishing process on a sapphire optical element, use a confocal microscope to detect the surface morphology of the sapphire optical element, and select an optical element A with a smooth surface under the microscope after polishing without pits and scratches;

[0035] S2. Mix 99 vol% sulfuric acid and 90 vol% phosphoric acid in a volume ratio of 1:1 to obtain an inorganic acid solution, then immerse the sapphire optical element A in the solution, etch the sub-surface defect layer on the surface of the sapphire optical element A, and passivate the scratches, cracks and pits on the sub-surface of the sapphire optical element A by high-temperature wet etching. The etching time is 1 hour and the temperature is 220°C. At this time, the C-surface etching rate of the sapphire optical element A is about 1 μm / h; after the etching is completed, the etching solution is replaced with 90 vol% phosphoric acid and heated to 180°C, and then the sapphire optical element A is immersed in phosphoric acid that has been preheated to 180°C, the heating is stopped and the temperature is naturally cooled to room temperature to remove the reactants deposited on the surface of the sapphire optical element A;

[0036] S3, rinse the sapphire optical element A with surface deposits removed with high-purity water for 60 seconds, then soak it in 10% NaOH solution at 50°C, and process it in sequence with frequencies of 20kHz, 45kHz, 60kHz, 80kHz, 100kHz, and 135kHz, with each frequency working for 2 minutes, and then rinse it with high-purity water for 2 minutes;

[0037] S4. Prepare a immersion solution by mixing a surfactant (composed of 25%wt of tetrasodium ethylenediaminetetraacetic acid, 15%wt of ammonium xylenesulfonate, 15%wt of benzenesulfonic acid, 0.5%wt of sodium hydroxide and 44.5%wt of water) and deionized water in a volume ratio of 1:10, immerse the sapphire optical element A in the immersion solution, and immerse it with multi-band ultrasound. The ultrasonic frequencies used during immersion are 20kHz, 45kHz, 60kHz, 80kHz, 100kHz, and 135kHz, respectively. The working time of each frequency is 10min, for a total of 60min. Then, ultrasonic cleaning is carried out with high-purity water. The ultrasonic frequencies used during ultrasonic cleaning are 20kHz, 45kHz, 60kHz, 80kHz, 100kHz, and 135kHz, respectively. The working time of each frequency is 2min. Finally, rinse with ultrapure water spray for 5min and dry naturally.

[0038] from Figure 1-3 It can be seen that the sapphire optical element A after post-processing has staggered scratch-like defects, and the morphology of the defects is smooth without sharp protruding structures.

[0039] from Figure 4 It can be seen that the exposed subsurface defect depth is less than 1 μm, indicating that the subsurface defect depth of this component is relatively shallow.

[0040] Example 2

[0041] A post-processing method for improving the high-voltage impact damage threshold of a sapphire optical element, comprising:

[0042] S1. Perform a pre-polishing process on a sapphire optical element, use a confocal microscope to detect the surface morphology of the sapphire optical element, and select an optical element B with a smooth surface under the microscope after polishing without pits and scratches;

[0043] S2. An inorganic acid solution is obtained by mixing 99 vol% sulfuric acid and 90 vol% phosphoric acid in a volume ratio of 3:1, and then the sapphire optical element B is immersed in the solution to etch the sub-surface defect layer on the surface of the sapphire optical element B. The scratches, cracks and pits on the sub-surface of the sapphire optical element B are passivated by high-temperature wet etching. The etching time is 1 hour and the temperature is 220°C. At this time, the etching rate of the C surface of the sapphire optical element B is about 1 μm / h. After the etching is completed, the etching solution is replaced with 90 vol% phosphoric acid and heated to 180°C. Then, the sapphire optical element B is immersed in phosphoric acid that has been preheated to 180°C, the heating is stopped, and the temperature is naturally cooled to room temperature to remove the reactants deposited on the surface of the sapphire optical element B.

[0044] S3, rinse the sapphire optical element B with surface deposits removed with high-purity water for 60 seconds, then soak it in 10% NaOH solution at 50°C, and process it with frequencies of 20kHz, 45kHz, 60kHz, 80kHz, 100kHz, and 135kHz in sequence, with each frequency working for 2 minutes, and then rinse it with high-purity water for 2 minutes;

[0045] S4. Prepare a immersion solution by mixing a surfactant (consisting of 25%wt of tetrasodium ethylenediaminetetraacetic acid, 15%wt of ammonium xylenesulfonate, 15%wt of benzenesulfonic acid, 0.5%wt of sodium hydroxide and 44.5%wt of water) and deionized water in a volume ratio of 1:10, immerse the sapphire optical element B in the immersion solution, and immerse it with multi-band ultrasound. The ultrasonic frequencies used during immersion are 20kHz, 45kHz, 60kHz, 80kHz, 100kHz, and 135kHz, respectively. The working time of each frequency is 10min, totaling 60min; then use high-purity water for ultrasonic cleaning. The ultrasonic frequencies used during ultrasonic cleaning are 20kHz, 45kHz, 60kHz, 80kHz, 100kHz, and 135kHz, respectively. The working time of each frequency is 2min. Finally, use ultrapure water spray to rinse for 5min and dry naturally.

[0046] from Figure 5-6 It can be seen that the surface morphology of the sapphire optical element B after post-processing has a structure extending downward, and the defect depth is greater than 1 μm. The difference between this embodiment and embodiment 1 is that in step 2, 99 vol% sulfuric acid and 90 vol% phosphoric acid are in a volume ratio of 3:1. When the sulfuric acid ratio is higher, the etching speed is faster, and for components with deeper sub-surface defects during processing, the defects can be more fully exposed.

[0047] Example 3

[0048] A post-processing method for improving the high-voltage impact damage threshold of a sapphire optical element, comprising:

[0049] S1. Perform a pre-polishing process on a sapphire optical element, wherein an abrasive with a lower hardness is selected during polishing, and a confocal microscope is used to detect the surface morphology of the sapphire optical element, and an optical element C with a smooth surface without pits and scratches under a microscope after polishing is selected;

[0050] S2, using 99 vol% sulfuric acid and 90 vol% phosphoric acid in a volume ratio of 1:3 to obtain an inorganic acid solution, then immersing the sapphire optical element C in the solution, etching the sub-surface defect layer on the surface of the sapphire optical element C, and passivating the scratches, cracks and pits on the sub-surface of the sapphire optical element C by high-temperature wet etching, the etching time is 1 hour, the temperature is 220°C, at this time, the C-surface etching rate of the sapphire optical element C is about 1μm / h; after the etching is completed, the etching solution is replaced with 90 vol% phosphoric acid and heated to 180°C, and then the sapphire optical element C is immersed in phosphoric acid that has been preheated to 180°C, the heating is stopped and the temperature is naturally cooled to room temperature to remove the reactants deposited on the surface of the sapphire optical element C;

[0051] S3, rinse the sapphire optical element C with surface deposits removed with high-purity water for 60 seconds, then soak it in 10% NaOH solution at 50°C, and process it with frequencies of 20kHz, 45kHz, 60kHz, 80kHz, 100kHz, and 135kHz in sequence, with each frequency working for 2 minutes, and then rinse it with high-purity water for 2 minutes;

[0052] S4. Prepare a immersion solution by mixing a surfactant (composed of 25%wt of tetrasodium ethylenediaminetetraacetic acid, 15%wt of ammonium xylenesulfonate, 15%wt of benzenesulfonic acid, 0.5%wt of sodium hydroxide and 44.5%wt of water) and deionized water in a volume ratio of 1:10, immerse the sapphire optical element C in the immersion solution, and immerse it with multi-band ultrasound. The ultrasonic frequencies used during immersion are 20kHz, 45kHz, 60kHz, 80kHz, 100kHz, and 135kHz, respectively. The working time of each frequency is 10min, for a total of 60min. Then, ultrasonic cleaning is carried out with high-purity water. The ultrasonic frequencies used during ultrasonic cleaning are 20kHz, 45kHz, 60kHz, 80kHz, 100kHz, and 135kHz, respectively. The working time of each frequency is 2min. Finally, rinse with ultrapure water spray for 5min and dry naturally.

[0053] from Figure 7-9It can be seen that the surface of the sapphire optical element C has no pits and scratches before post-processing, and the surface of the sapphire optical element C after post-processing is densely covered with smooth small pits and scratches.

[0054] from Fig.10 It can be seen that the depth of the exposed subsurface defects is less than 500nm, indicating that the depth of the subsurface defects of this component is relatively shallow. The difference between this embodiment and embodiment 1 is that in step 2, 99vol% sulfuric acid and 90vol% phosphoric acid are in a volume ratio of 1:3. When the sulfuric acid ratio is low, the etching speed is slower, and the exposed passivated subsurface defects are smoother. For components with shallow subsurface defects during processing, there will be no over-etching, and the passivation fluctuations are smoother, which is conducive to performance improvement.

[0055] Comparative Example 1

[0056] This comparative example is a sapphire optical element that has only undergone a pre-polishing process but no post-processing.

[0057] 30 sapphire optical components were post-processed according to the method of Example 1, and 30 sapphire optical components were processed according to the method of Comparative Example 1, and then the bending strength was tested according to the national standard GBT6569-2006. Figure 11-Figure 12 As shown, from Fig.11 It can be seen that the bending strength of sapphire optical components without post-treatment is mainly distributed in the range of 600MPa to 900MPa, with an average value of 699.4MPa, and the bending strength is average; the bending strength distribution of sapphire optical components after post-treatment is as follows Fig.12 As shown, it is mainly distributed in the range of 900-1300Mpa, with an average value of 1082Mpa, and the bending strength is greatly improved.

[0058] Comparative Example 2

[0059] The difference between this comparative example and Example 1 is that the volume ratio of sulfuric acid to phosphoric acid in S2 is 5:1, and the rest is consistent with Example 1. The surface morphology of the sapphire optical element was detected by confocal microscopy, and it was found that the sapphire optical element etched by the ratio of sulfuric acid to phosphoric acid in this comparative example was over-etched, and the longitudinal depth of the sapphire sub-surface defects was deeper and the morphology was sharper, thereby reducing the impact resistance of the sapphire optical element.

[0060] Comparative Example 3

[0061] The difference between this comparative example and Example 1 is that the volume ratio of sulfuric acid to phosphoric acid in S2 is 1:5, and the rest is consistent with Example 1. The surface morphology of the sapphire optical element was detected by confocal microscopy, and it was found that the sapphire optical element etched by the ratio of sulfuric acid and phosphoric acid in this comparative example had a slow etching rate, and at the same reaction temperature, the etching in the depth direction was incomplete, and the scratches, cracks and pits on the surface of the sub-sapphire optical element could not be effectively passivated, which resulted in these hidden scratches, cracks and other damage defects still acting as damage precursors, forming microcracks, resulting in a low fatigue life of the element under pressure shock, and it is very easy to be seriously damaged.

[0062] Comparative Example 4

[0063] The difference between this comparative example and Example 1 is that in S2, after etching and passivating the sapphire optical element with sulfuric acid and phosphoric acid, the etching solution is replaced with 100°C deionized water to rinse the element, and then placed in boiling deionized water, heating is stopped and the temperature is naturally cooled to room temperature, and the other steps are consistent with Example 1. In this comparative example, since deionized water is used to clean the insoluble matter produced by the previous high-temperature wet etching, the insoluble aluminum sulfate trihydrate produced by the high-temperature etching cannot be completely cleaned. Since the insoluble matter is not fully removed, the sub-surface defects are not effectively passivated, resulting in the failure to effectively improve the mechanical properties.

[0064] Comparative Example 5

[0065] The difference between this comparative example and Example 1 is that in S3, after rinsing with high-purity water, deionized water is used for soaking, and the rest is the same as Example 1. In this comparative example, since NaOH is not used to soak the sapphire optical element, phosphoric acid is not completely removed and adheres to the surface of the element. The subsequent surfactant and high-purity water treatment process is difficult to completely rinse the phosphoric acid, which will affect the cleanliness of the optical element.

[0066] Comparative Example 6

[0067] The difference between this comparative example and Example 1 is that in S3 and S4, only 20kHz, 80kHz or 135kHz ultrasonic frequencies are used during ultrasonic treatment, and the other steps are consistent with Example 1. Since this comparative example does not use multi-band ultrasonic treatment, but only uses 20kHz, 80kHz or 135kHz ultrasonic frequencies, this will result in incomplete cleaning of the component surface, such as Fig.13 Wiping the sapphire surface with alcohol cannot effectively remove these insoluble substances, which will affect the transmittance of the optical element.

[0068] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A post-processing method for improving the high-voltage impact damage threshold of sapphire optical elements, characterized in that: The following steps are involved: S1. Use confocal microscopy to detect the surface morphology of sapphire optical components; S2, heating and etching the sapphire optical element using an inorganic acid solution; Then the etching solution is replaced with phosphoric acid to remove the reactants deposited on the surface of the sapphire optical element; S3, the sapphire optical element with surface deposits removed is rinsed with high-purity water, then immersed in NaOH solution, supplemented with multi-band ultrasonic treatment, and then rinsed with high-purity water; S4. Soak the sapphire component in a surfactant and treat it with multiple frequency bands of ultrasonic waves. Finally, use high-purity water for ultrasonic cleaning and direct rinsing, and dry it naturally.

2. The post-processing method for improving the high-voltage impact damage threshold of a sapphire optical element according to claim 1, characterized in that: In S2, the inorganic acid solution is a mixed acid of sulfuric acid and phosphoric acid, the mixing ratio is sulfuric acid: phosphoric acid = 4:1 to 1:4, the etching time is 5 to 300 minutes, the temperature is 200 to 240°C, the sulfuric acid concentration is 95 to 99 vol%, and the phosphoric acid concentration is 80 to 90 vol%.

3. The post-processing method for improving the high-voltage impact damage threshold of sapphire optical elements according to claim 1, characterized in that: In S2, the temperature of phosphoric acid when removing surface deposits is 160-220° C. After the optical element is placed in the solution, heating is stopped and the solution is cooled naturally to room temperature.

4. The post-processing method for improving the high-voltage impact damage threshold of a sapphire optical element according to claim 1, characterized in that: In the S3, first rinse with high-purity water for 10 to 60 seconds, the concentration of NaOH solution is 5% to 15%, the soaking temperature is 30 to 50°C, the soaking is 10 to 60 minutes, the ultrasonic frequency is 20kHz to 135kHz and at least two frequencies are selected during ultrasonic treatment, and finally rinse with high-purity water for 1 to 5 minutes.

5. The post-processing method for improving the high-voltage impact damage threshold of sapphire optical elements according to claim 1, characterized in that: In S4, when using surfactant for soaking, the soaking liquid is prepared according to the ratio of surfactant to deionized water = 1:10, and the soaking is carried out for 30 to 60 minutes. Ultrapure water is then used for ultrasonic cleaning, and the ultrasonic frequency is 20kHz to 135kHz. At least two frequencies are selected during ultrasonic treatment, and the cleaning is carried out for 30 minutes. Finally, ultrapure water is sprayed for rinsing for 5 to 10 minutes, and the mixture is dried naturally.

6. The post-processing method for improving the high-voltage impact damage threshold of a sapphire optical element according to claim 1, characterized in that: In the S4, the surfactant includes 10% wt to 25% wt of tetrasodium ethylenediaminetetraacetate, 5% wt to 15% wt of ammonium xylenesulfonate, 5% wt to 15% wt of benzenesulfonic acid, 0.05% wt to 0.5% wt of sodium hydroxide and 44.5 to 69.95% wt of water.

Citation Information

Cited By

  • Weak measurement-based high-temperature pressure detection method and sapphire microstructure sensor

    CN121855737A